Pemanfaatan Sensor Suhu LM 35 Berbasis Microcontroller ATmega 8535 pada Sistem Pengontrolan Temperatur Air Laut Skala Kecil - Indriani, Anizar; Johan, Johan; Witanto, Yovan; Hendra, Hendra (Rekayasa Mesin, 2014)
System of temperature control are used in many facility such as room temperature control, quality control of food and drink, electronic equipment control and etc. control of temperature can be done by using microcontroller as a media processing and process the changes of temperature that occured to the voltage. One of supporting component on the microcontroller to detect the change of temperature is temperature sensor LM 35 which in this study we will focus on the temperature sensor LM 35 for detect of change of temperature on the sea water in a small scale. the purpose of this study is to determine the ability and performance of temperatur sensor LM 35 for detect the changes of temperature sea water and check the condition of temperatur sensor LM 35 in use on the sea water. The results show that the temperature sensor of LM 35 can be used to measure the changes of temperatur sea water without have higher difference on the actual value and experiment results. the range of difference is smaller and the temperature sensor of LM 35 can be used to measured the change of temperature of sea water.Keywords: LM 35 Sensor, Microcontroller ATmega 8535, Sea Water Temperature